Prediction and its Epistemic Value in the Natural Sciences of the 19th century. - Christopoulou, Vasiliki (Neusis, 2025)
This paper examines the concept of prediction in the natural sciences, primarily in Britain during the 19th century. Although prediction is considered a fundamental element of science, and its value is often taken for granted, this article explores its role without presupposing its unquestionable epistemic value. Additionally, this paper examines prediction across various scientific fields such as astronomy, physics, chemistry, and biology. The paper then focuses on two key issues. The first is the relationship between mathematization, the hypothetico-deductive model of science, and prediction. The second concerns “desciptivism,” as termed by the historian of science John Heilbron, in late 19th-century physics and how it redefined the epistemic value of prediction in science.